2021
DOI: 10.1111/jfbc.13852
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polyphenols in Aegle marmelos leaf and ameliorative efficacy against diabetic mice through restoration of antioxidant and anti‐inflammatory status

Abstract: The biomedical survey reports edible plant Aegle marmelos has been utilized for centuries by tribal communities in India as a dietary supplement for the management of diabetes. Herein, we have investigated cytotoxicity, cytoprotective and antidiabetic activity of characterized alkaloid-free hydroalcoholic extract of A. marmelos (AFEAM; 200 and 400 mg/kg).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The oxo-inflammatory, metabolic status, and beta-cell function are improved by quercetin and sitagliptin co-treatment (Al-Ishaq et al, 2019). Furthermore, quercetin regulates the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) and inhibits the actions of a tyrosine kinase inhibitor, which together improve glucose-stimulated insulin secretion and have antidiabetic effects (Ibrahim et al, 2022).…”
Section: Ppi Network Of Targeted Genes and Understanding The Ac On Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…The oxo-inflammatory, metabolic status, and beta-cell function are improved by quercetin and sitagliptin co-treatment (Al-Ishaq et al, 2019). Furthermore, quercetin regulates the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) and inhibits the actions of a tyrosine kinase inhibitor, which together improve glucose-stimulated insulin secretion and have antidiabetic effects (Ibrahim et al, 2022).…”
Section: Ppi Network Of Targeted Genes and Understanding The Ac On Me...mentioning
confidence: 99%
“…Gallic acid enhances the level of insulin and antioxidant enzymes (superoxide dismutase; SOD, glutathione; GSH, and catalase; CAT) and lowers lipid peroxidation, inflammation, oxidative stress, and glucose levels by activating the AMPK pathway and subsequently activating and also protecting beta-cell damages. Besides that, it can inhibit gluconeogenic genes like phosphoenolpyruvate carboxykinase and glucose 6phosphatase and activate the protein kinase B (PKB or Akt) pathway, lowering levels of glycaemia and insulin resistance ( ; Silveira et al, 2018) (Ibrahim et al, 2022;Silveira et al, 2019).…”
Section: Ppi Network Of Targeted Genes and Understanding The Ac On Me...mentioning
confidence: 99%
“…Furthermore, the strong interaction of gymnemic acid with α-amylase and α-glucosidase suggested that G. sylvestre reduced carbohydrate digestion and absorption. It is also reported that these compounds controlled insulin levels in the pancreatic beta-cells by enhancing the 5′ adenosine monophosphateactivated protein kinase pathway [32,33]. Furthermore, previous ndings also suggested that gymnemic acid may control oxo-in ammations, insulin resistance, and glucose metabolism, which are bene cial for the of diabetes.…”
Section: Molecular Docking Analysismentioning
confidence: 92%
“…Last but not least, the ionization process, source of ionization, and flighting distance and time need to be adjusted and favored also based on the chemical nature and complexity of the metabolites. Moreover, the repeatability of the optimized or non-optimized chromatographic and spectroscopic methods needs to be validated to reproduce robustness [ 31 ].…”
Section: Review Findingsmentioning
confidence: 99%